PROGRESS Intervention: Increasing Prosocial and Respect to Prevent Bullying and Radicalism in Schools - Muthia Aryuni; I Nyoman Sudana Degeng; Marthen Pali; Imanuel Hitipeuw (STAI Hubbulwathan Duri, 2024)
Bullying and radicalism share common ground as forms of antisocial behavior characterized by violence. This study evaluates the effectiveness of the PROGRES intervention, designed to enhance prosocial and respectful attitudes and increase knowledge about bullying and radicalism among fifth-grade students. Employing a pre-posttest control group design with 150 students from urban elementary schools, this research utilized hypothesis testing through Independent Sample T-test and Paired Sample T-test. Results indicated that the PROGRES intervention significantly increased prosocial attitudes by 92.53%, respectful attitudes by 94.15%, and knowledge about bullying and radicalism by 98.12% and 97.01%, respectively (p 0.05 for all). These findings suggest that the PROGRES intervention could play a crucial role in educational strategies to combat bullying and radicalism, emphasizing its potential incorporation into school curricula nationwide.